Sensitive data protection and App use for women's well-being. A question of awareness (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article addresses the issue of APPs dedicated to women's health and well-being from the perspective of the legal rules applicable to the processing of personal data in light of Regulation (EU) 2016/679. Particular attention is paid to the topic of digital education in view of the fact that the main users of these devices are girls.
Keywords: Health Mobile App; Regulation (EU) 2016/679; data protection; teenagers; digital literacy